Rapamycin inhibits oral cancer cell growth by promoting oxidative stress and suppressing ERK1/2, NF-κB and beta-catenin pathways - Semlali, Abdelhabib; Papadakos, Sofia; Contant, Camille; Zouaoui, Ikram; Rouabhia, Mahmoud (Frontiers in Oncology, 2022)
Treatment of oral cancer is based exclusively on surgery combined with or without chemotherapy. However, it has several side effects. Targeting a new, more effective therapy has become an urgent matter. The purpose of this study was to evaluate the anti-tumor activity of rapamycin in oral cancer and its mechanism of action. Human gingival carcinoma cells were stimulated with different concentrations of rapamycin to assess proliferation, colony formation, cell migration as well as apoptosis and autophagy. The expression of proteins involved in the cell cycle (cyclin D1, p15, p21, p27) and autophagy as well as that of oncogenes and tumor suppressor genes were determined by quantitative PCR. The signaling pathways were evaluated by Western blotting. Our results show that rapamycin has a selective effect at a low dose on cancer cell growth/survival. This was confirmed by low colony formation and the inhibition of cell migration, while increasing cell apoptosis by activating caspase-9 and -3. Rapamycin promoted cell autophagy and increased mitochondrial oxidative stress by being involved in DNA damage in the exposed cells. Finally, rapamycin exhibits potent anti-oral cancer properties through inhibition of several cancer-promoting pathways (MAPK, NF-κB and Wnt/Beta Catenin). These results indicate that rapamycin could be a potential agent for the treatment of oral cancer and for a prevention strategy.